China's economic miracle does FDI matter? - Tang, Sumei; Selvanathan, Eliyathamby A.; Selvanathan, Saroja; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 2012)
This insightful book analyses the impact of Foreign Direct Investment (FDI) in China as well as making valuable contributions to the theory of FDI more broadly. The authors provide empirical analysis of key factors including the location-specific determinants of FDI; the impact of FDI on domestic investment, income distribution, consumption and tourism; the relationship between FDI inflows and income inequality; causality between FDI, domestic investment and economic growth; and causality between FDI and tourism. The study concludes that FDI plays a crucial and positive role in the economic development of China. Rather than crowding out domestic investment, FDI is found to stimulate economic growth by complementing it.
1. Introduction -- 2. Theories of FDI on multinational enterprises and related empirical studies on China -- 3. Extensions on the theory of FDI to host countries and empirical studies on the impact of FDI -- 4. Location determinants of FDI -- 5. FDI, domestic investment and economic growth -- 6. The relationship between FDI and tourism -- 7. Tourism and economic growth -- 8. FDI and regional income inequality -- 9. FDI spill-over effects on consumption -- 10. FDI and its overall impact in China.
Includes bibliographical references and indexes.
Keywords: Investments, Foreign -- China; China -- Economic conditions; Electronic books